Purwarupa Sistem Komunikasi Angkot sebagai Optimasi Transportasi Perkotaan dengan Metode Routing Multi-Hop berbasis Sistem Notifikasi - Muhammad Naufal Aziz Huryansyah; Rakhmadhany Primananda; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Angkutan kota is public transportation that can carry out mobility at affordable prices, but angkot operations generally do not have special infrastructure and angkot does not have a communication system or notification about the state of the next stop, the behavior of angkot drivers often stops at inappropriate places to wait for passengers causing inefficiency on this transport. It is different with Bus Rapid Transit, which has infrastructure and communication systems but cannot reach certain places that angkot can reach. The purpose of this research is to design, adapt, test, and find out whether the adaptation of the concept of Bus Rapid Transit can be applied to angkot. This research is useful to provide an overview of the adaptation of the BRT system concept by adapting the driver assist and automation and passenger information aspects to be applied to Angkots with a notification mechanism for passengers at the halte and information on the estimated time of the Angkot arrival so that the driver gets assists automatically regarding this information. The system is implemented as a prototype of a central system, angkot and halte system, the system can relay multi-hoping angkot arrival information using the ESPNOW delivery protocol and send passenger notifications published by the halte to the central system with the MQTT delivery protocol on the 802.11 communication network. The result is that the prototype can detect passengers at the bus stop then send notifications and can relay messages in multi-hop between halte.